Finding god in Dinsman’s it is not a suicide: an Islamic metaphysical approach - Mas Rynna Wati Ahmad, (Penerbit UKM, 2013)
Dinsman, whose real name is Che‟ Shamsuddin Othman, was known for his experimentation on the absurd theatre techniques during the period of Experimental Theatre in Malaysia in the 1970‟s. His play It Is Not A Suicide reflects strong philosophical underpinnings that highlight the deep emotional setbacks experienced by an individual who is caught in the tumult of finding the right path. Even though his experimentation seems to be vague to many scholars and theatre critics, his appropriation of absurd theatre techniques had successfully transformed a play that was once known to be atheistic in nature to be distinctively his own. Unfortunately, his experimentations on absurd theatre were not clearly understood by many. This is because most theatre critics and local audience remain sceptical towards the fundamental philosophy of the absurd. As a result, the concept of the Malay absurd in Modern Malay theatre is still not fully received. Although the intellectual and religious maturity of the audience and the theatre scholars has grown over the years, the view of absurd works being pessimistic remains. For the purpose of this paper, the author focuses on Dinsman‟s It Is Not A Suicide; reading it through the lens of Al-Ghazali‟s The Alchemy of Happiness. Through the Islamic metaphysical approach, this article offers a more optimistic perspective to his work. It argues that the play still functions within the Islamic parameters thus eliminating the atheistic label which clouded this work for more than three decades.